2020
DOI: 10.23958/ijssei/vol06-i12/257
|View full text |Cite
|
Sign up to set email alerts
|

Covid Impact on Small Business

Abstract: The sudden attack of COVID-19 has affected human lives and economies to a great extent. The lockdown and restrictions taken as measures by the government to stop the spread of the coronavirus are responsible to shut down many small businesses permanently. In this paper, we will get an idea of how the pandemic has affected small businesses. The world witnessed the largest fall in the number of active businesses. The supply chain got affected due to this and as a result, this affected global trade. Research show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 1 publication
3
20
0
6
Order By: Relevance
“…These findings are consistent with prior research that evaluated the response of small businesses to the pandemic ( Bartik et al , 2020 ; Fairlie, 2020 ; Kalogiannidis, 2020 ). Bartik et al (2020) found that 43% of the small businesses in their study closed temporarily due to COVID-19, and that businesses with in-person services were more negatively affected than those with less person-to-person interactions.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with prior research that evaluated the response of small businesses to the pandemic ( Bartik et al , 2020 ; Fairlie, 2020 ; Kalogiannidis, 2020 ). Bartik et al (2020) found that 43% of the small businesses in their study closed temporarily due to COVID-19, and that businesses with in-person services were more negatively affected than those with less person-to-person interactions.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, the small business enterprises in this study were likely to face a possibility of real shutdown, and very few small-sized business enterprises were found to overcome the second wave of the pandemic. A study by Kalogiannidis (2020) also confirmed that small businesses might be at risk and face the practical possibility of bankruptcy due to long lockdowns. Moreover, even small businesses in European countries which benefited from their country's good financial schemes also faced financial crisis, and very few of them could survive repetitive and long-lasting lockdowns (García et al 2020;Parikh 2020).…”
Section: Domino Effects Of Covid-19 On the Local Tourism Industrymentioning
confidence: 81%
“…According to a consumer survey conducted by AECOC in April 2020, the economic crisis caused by the COVID-19 pandemic was the most significant Spain has experienced since 2008 [62]. Changes in the economy, manufacturing, technology and service sectors were observed [137][138][139][140][141]. During this time, interest in PLs has increased.…”
Section: General Remarksmentioning
confidence: 99%